Application of Innovative Technologies to Physical Education and Sports - Mansurovich, Salixov Shoxrux (Researchparks Publishing, 2023)
In this article, the problems encountered in fitness physical training and sports competitions focused on high results. Areas aimed at solving problematic situations and, first of all, such issues as the direction of digitization and innovative technologies to sports and physical education are covered.